Case Report: Catheter-Directed Endovascular Thrombolysis for Refractory Cerebral Venous Sinus Thrombosis in a Patient With Behçet Disease - Xu, Yongfeng; Qiu, Minjian (Frontiers in Neurology, 2021)
Background: Behçet disease (BD) is an autoimmune and vasculitic disorder. BD affects the veins more frequently than the arteries. The cerebral venous sinus thrombosis (CVST) was reported to occur in about 20% of neuro-BD. Huge dilemma exists in the treatment of CVST with BD, some of which were refractory to the standard therapy. Case Presentation: Here, we report a BD case with refractory intracranial hypertension caused by CVST which is successfully treated with catheter-directed endovascular thrombolysis. Before endovascular thrombolysis, intravenous pulse methylprednisolone combined with anticoagulant therapy was used, and resulted in limited effects. Conclusion: We conclude that catheter-directed thrombolysis may be considered for refractory CVST with BD, provided that coexistent pulmonary and cerebral artery aneurysms are ruled out.